Venous Sinus Thrombosis due to Vaccine-Induced Thrombotic Thrombocytopenia (VITT): A Case Report. Issue 1 (June 2022) - Ramrakhiani, Neetu; Mamodia, Palak; Sharma, Devang; Agarwal, Nitesh
Patient, 19-year-old male, presented with fever, abdominal pain, headache, and vomiting presented after vaccination with ChAdOx1 CoV-19 (AstraZeneca, University of Oxford, and Serum Institute of India, and adenoviral-based vaccine) with alteration in sensorium and thrombocytopenia. He was diagnosed to have extensive venous sinus thrombosis with mass effect, midline shift, and underwent decompressive hemicraniotomy. He had a good outcome.